Golongan Putih (GolputT) Menurut Hukum Islam (analisis terhadap Al-Qur’an dan Hadits) - Muhammad Arsad Nasution (AL-ISTINBATH : Jurnal Hukum Islam, 2017)
Islam is very important leadership inexistence. This is evident from the many verses of the Koran and the hadith that explains about leadership. Beside that politically Islamic law can not be applied to the surface of the earth when there is no power to compelen forcement. That power is the master that made Islamic law as the supreme law governing the country. The existence of Islamic law would not be important if he had only beenon the writings of scholars of Islamic law. Islamic law new significanceseen when he practiced and carried out by human beings. Thus Islamic law requires the authorities wh oimplement it. The appointment of rulers who are committed to the enforcement of Islamic law chosen by democratic ballot. Suffrage some one will be very significant in determining the leadership. Therefore abstentions are not justified under Islamic law.